AB0968 Construct Validity of New Ultrasound Score Intended to Measure Damage of Small Joints in Patients with Rheumatoid Arthritis. (10th June 2014) - Radunovic, G.; Porta, F.; Prodanovic, S.; Seric, S.; Gavrilov, N.; Grujic, M.; Prodanovic, S.; Matucci-Cerinic, M.; Damjanov, N.
Abstract : Background: Gray scale ultrasound (US) detects from 2 up to 9 times more erosions on B mode scans than standard radiographs of hand and feet in patients with rheumatoid arthritis (RA). Nowadays, mainly for research purposes, US erosions of small joints were semiquantitatively scored 0–3 according to the Szkudlarek and Scoring by UltraSound Structural erosion (ScUSSe) systems, respectively. Objectives: To assess the construct validity of new US erosion score (USES) and ability of new method to detect erosions of small joints in patients with RA as well as to suggest a new USES for erosion quantification. Methods: Sixty-three patients (48 females and 15 males) with clinically active disease were prospectively recruited at the Institute of Rheumatology, Belgrade, Serbia. All of them were treated with Methotrexate, or with other DMARDs, including biologic agents. The study was conducted in agreement with the Declaration of Helsinki and was approved by relevant ethics committee. The mean age of patients (S.D.) was 54.7 (12.7) years (range 24-78 years) and the mean disease duration was 28.8 (29.0) months (range 4-156 months). Forty-six pts (73.0%) were rheumatoid factor positive, and 45 pts (71.4%) anti-CCP positive. The patients underwent clinical and laboratory assessment, along with blinded power Doppler US (PDUS) and grey-scale (GS) US (GSUS) examination. A GSUS examination for presence, total surface, and total volume of erosions on 22 joints (2 wrists, 10 metacarpophlangeal joints – MCPs, and 10 metatarsophalangeal joints – MTPs) was performed by two independent examiners, blinded to clinical findings. GSUS examinations were based on standard EULAR reference scans, using US workstation Esaote My Lab 70xvg with 18 MHz linear probe. Surface USES (sUSES) was calculated as a sum of multiplications of long axis with short axis diameters of erosions, and volumetric USES (vUSES) as a sum of multiplications of long axis diameter, short axis diameter, and depth diameter of erosions. Results: Five thousand five hundred and forty-four joint quadrants and 1386 joints were examined by two ultrasound operators. Erosions were detected by US in 264 (19, 0%) joints. Strong positive linear correlation was found between s USES, vUSES and standard radiographic damage index, such as Sharp van der Heijde score (r=0.66, and r=0.67, respectively, p<0.001). Correlations between sUSES and vUSES with DAS28, HAQ, levels of ESR and CRP were weak and statistically insignificant, except between sUSES with serum levels of CRP (r=0.30, p<0.02). Conclusions: Owing to our findings of strong positive linear correlation with the most utilized radiographic score (Sharp van der Heijde score), surface and volumetric ultrasound erosion scores showed at least decent ability to measure damage of hand and feet joints in patients with rheumatoid arthritis. Our next step in development of ultrasound erosion scores will be assessment of reliability and sensitivity to change of these scores in patients with early rheumatoid arthritis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2918